The Outcomes in Patients Treated With Intratympanic and Systemic Steroids for Sudden Hearing Loss and Prognostic Factors - Bel Çeçen, Ayse; Kemal, Ozgur; Terzi, Ozlem; Taştan, Mustafa (ENT Updates, 2021)
Objective: Steroid therapy is the gold standard in treating sudden sensorineural hearing loss (SSNHL). This study aimed to compare the results of the systemic and intratympanic administration of steroids used to treat patients with SSNHL. Methods: A retrospective analysis was performed with 90 patients treated for SSNHL in our clinic between 2014 and 2017. Intratympanic steroid (ITS) was administered to 44 patients and systemic administration (intravenous or oral) to 46. Pure-tone average (PTA) values were recorded before treatment and at the first and third months post-treatment. Hearing improvement was evaluated according to the Furahashi criteria. Results: The pre-treatment PTA values were 68.9 ± 25.9 dB in the systemic steroidtreated group and 79.0 ± 22.6 dB in the intratympanic steroid-treated group, with no statistically significant difference determined (P = .07). After 1 month of treatment, the PTA median value was 6.0 (from −23.0 to −65.0) dB in the systemic group; and the median was 7.5 dB (from −13.0 to −84.0) in the intratympanic group. No statistically significant difference was determined between the groups in terms of regression in pure-tone median values after treatment (P = .90). According to the Furahashi criteria, in the evaluations between the 2 groups, those with complete improvement and significant improvement were compared together, and those with mild improvement and those without improvement were compared separately. There was no statistically significant difference in the distribution with respect to healing, between the groups (P = .692). Conclusion: Although steroids––which are the only treatment with proven efficacy in sudden idiopathic hearing loss––are effective in the improvement of hearing, the methods of administration showed no differences in terms of effectiveness.